2007
DOI: 10.1097/ico.0b013e31805444ba
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Corneal Hydrops Secondary to Keratoconus With Intracameral Injection of Sulfur Hexafluoride (SF6)

Abstract: Early intervention with intracameral SF6 injection is a safe and effective therapy for early reduction of corneal edema in eyes with keratoconus and acute hydrops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 10 publications
2
33
0
4
Order By: Relevance
“…39 Various studies have shown a significantly faster resolution time with use of these agents as compared with conventional therapy in acute hydrops with keratoconus as well as a few case reports in eyes of kerotoglobus. 36,[40][41] A study by Basu et al 41 found that the resolution time did not show much difference between conventional and intracameral perfluoropropane treatment in cases of pellucid marginal degeneration and keratoglobus. They felt that this may have been due to location of breaks in these cases as well as the usually larger, more extensive breaks associated with keratoglobus.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Various studies have shown a significantly faster resolution time with use of these agents as compared with conventional therapy in acute hydrops with keratoconus as well as a few case reports in eyes of kerotoglobus. 36,[40][41] A study by Basu et al 41 found that the resolution time did not show much difference between conventional and intracameral perfluoropropane treatment in cases of pellucid marginal degeneration and keratoglobus. They felt that this may have been due to location of breaks in these cases as well as the usually larger, more extensive breaks associated with keratoglobus.…”
Section: Treatmentmentioning
confidence: 99%
“…Use of air, sulphur hexafluoride, and perfluoropropane has been described. [36][37][38][39][40][41] The gas is thought to act as a mechanical barrier to fluid entry into the corneal stroma, as well as a tamponading agent in re-opposing the rolled, detached edges of the Descemet's tear. This is theoretically felt to aid in endothelial migration across the tear.…”
Section: Treatmentmentioning
confidence: 99%
“…Conventional treatment includes bandage contact lens, topical hypertonic saline and cycloplegics [3]. More invasive is the use of intracameral gas to tamponade the detached descemet's membrane to the posterior surface of the corneal stroma [4] [5]. Regarding the surgical management of keratoglobus, no golden standard has been defined.…”
Section: Discussionmentioning
confidence: 99%
“…1 Conventionally, acute hydrops is treated medically with topical antibiotic, hypertonic saline, cycloplegic with or without a bandage contact lens. However, there is emerging evidence suggesting that an earlier resolution of corneal oedema could be facilitated by intracameral injection of air, 2 sulphur hexafluoride (SF 6 ) 3,4 and perfluoropropane (C 3 F 8 ) gas. [5][6][7] The proposed mechanism is that the intracameral air or gas acts as a mechanical tamponade, helping the apposition of the Descemet's membrane and creating a barrier to prevent the entry of aqueous into the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the short-acting property of intracameral air or SF 6 gas injection can lead to premature disappearance of the gas resulting in inadequate treatment of the acute hydrops. [2][3][4] This means that additional intracameral injection is required to maintain its tamponading action.…”
Section: Introductionmentioning
confidence: 99%